Sleep responses of young swimmers to training load and recovery during tapering - Fernandes da Costa, M. S.; de Oliveira Damasceno, V.; Tulio de Melo, M.; Moura dos Santos, M. A.; Roberto dos Santos, W.; Veruska Narciso, F.; Romário dos Santos, W.; Melo de Oliveira, S. F.; Pinheiro Paes, P. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Tapering is a decisive phase in planning a young swimmer's preparation for competition. During this period, not only training loads, but also recovery, which includes sleep quality, must be constantly monitored. Objective: This study aims to investigate sleep behavior as a variable directly influenced by training load during the tapering phase of training for young swimmers. Methods: A polysomnography test was performed at the beginning of the tapering phase, as a baseline for sleep variables. In each daily training session, the overload and recovery variables were measured. The internal training load was evaluated in the PSE session and the external load by quantifying the training. The recovery variables were divided into the recovery variable, assessed using the TQR questionnaire, and sleep variables, which included sleepiness, scored using the Karolinska scale, and sleep behavior, using an actigraph and a sleep diary. Conclusion: It is concluded that there is no significant influence between training loads and sleep variables. However, a strong association was observed between TST and EL (External load), in the irregular sleep group.